MENENGOK SENI TEATER/DRAMA UMAT ISLAM DI INDONESIA - Aning Ayu Kusumawati (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
Theatre has become a part of the Islamic world recently. Moslems become more familiar with Islamic theatre and film. Indonesian independence, as well as the western theatre, triggers the blooming of theatre. To see its development in this country, where Moslems is the majority, it is necessary to observe how the local group of theatre or drama making its changes in their appreciation, conception, interpretation, expression, and creation. The main paradigm of the art of Islamic theatre, as the part of Islamic culture, can be understood through a textual and contextual approach.